Optimization and Synergy of Non-formal Islamic Education in the Three Centers of Islamic Education - Amrullah, Amrullah; Seraj, Prodhan Mahbub Ibna; Abd Al-lateef, Ghada Tosson; Galal, Mohammed (Yayasan Corolla Education Centre, 2023)
Since the very beginning, non-formal Islamic Education was recognized as an important part of the process of transmitting Islamic values to society. However, non-formal Islamic education implemented by educational institutions nowadays has not been able to transform optimally and synergize with the three centers of Islamic education (formal, informal, and non-formal) in realizing the overall educational goals. This research revealed how the format of optimizing non-formal Islamic education and its synergy with the three centers of Islamic education. Moreover, this study used a descriptive method with a library research approach, in which the research was carried out by reading and conducting a study of some scientific papers related to the problems mentioned. Based on the research result, it was found that in terms of regulation, non-formal education has full support from the Law of the National Education System Number 20 of 2003 Chapter VI Article 26 paragraphs 1 and 3, which stated that the implementation of non-formal education has a function as a substitute, addition, and/or complement to formal education to support lifelong education. Therefore, efforts to optimize and synergize non-formal Islamic education in the three centers of Islamic education were a form of addition and complement to formal and informal education, which of course still cannot be a substitute for the formal one. Besides, non-formal Islamic education is also an opportunity for developing the students' ability about Islamic science, and also as a support system when formal education has weaknesses both in terms of time and cost.